2014
DOI: 10.1002/jbm.b.33240
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and other property changes of retrieved sequentially annealed UHMWPE acetabular and tibial bearings

Abstract: This investigation analyzed retrieved sequentially crosslinked and annealed (SXL) ultra‐high molecular weight polyethylene bearings to determine whether the material is chemically stable in vivo. A series of retrieved tibial and acetabular components were analyzed for changes in ketone oxidation, crosslink density, and free radical concentration. Oxidation was observed to increase with in vivo duration, and the rate of oxidation in tibial inserts was significantly greater than in acetabular liners. SXL acetabu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 33 publications
1
44
2
Order By: Relevance
“…In contrast, a recent study has reported an increase in another modern free-radical containing highly crosslinked material that was not antioxidant-stabilized. 29 With minimal in vivo carbonyl retention, thus no oxidation present in these retrievals, this decrease in free radical content was likely related to the free radical scavenging activity of the vitamin E. Hydroperoxide index remained constant in the retrievals indicating that the oxidative cascade initiated during crosslinking was effectively quenched by the subsequent diffusion of vitamin E into the irradiated material. In real-time aging studies, it was observed that hydroperoxide content in vitamin E-diffused, irradiated UHMWPE decreased with time.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, a recent study has reported an increase in another modern free-radical containing highly crosslinked material that was not antioxidant-stabilized. 29 With minimal in vivo carbonyl retention, thus no oxidation present in these retrievals, this decrease in free radical content was likely related to the free radical scavenging activity of the vitamin E. Hydroperoxide index remained constant in the retrievals indicating that the oxidative cascade initiated during crosslinking was effectively quenched by the subsequent diffusion of vitamin E into the irradiated material. In real-time aging studies, it was observed that hydroperoxide content in vitamin E-diffused, irradiated UHMWPE decreased with time.…”
Section: Discussionmentioning
confidence: 91%
“…Unfortunately the remelting process can lead to mechanical properties near the American Society for Testing and Materials (ASTM) minima for surgical UHMWPE implants [13,14]. For this reason annealing is seen to be a viable alternative to allow free radicals to recombine in the amorphous regions of the polymer whilst still preserving the crystal structure and more importantly the mechanical properties [10,15]. Even so, free radicals in the crystalline regions do not readily recombine during annealing thus leading to the potential for oxidation.…”
mentioning
confidence: 97%
“…The sequential irradiation process of 30 kGy followed by annealing being repeated 3 times over, is reported to provide the optimum mechanical properties whilst producing an oxidatively stable material [16]. In accelerated aging tests oxidative stability has been demonstrated, however more recently the relevance of such testing has come into question as retrieved sequentially irradiated devices have shown signs of oxidation [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Radiostereometric analysis of THAs using sequentially annealed secondgeneration HXLPE liners suggested that head penetration and threedimensional wear remained low at 5 years [1]. However, recent retrieval studies [2,3] stressed the persistence of oxidation in the HXLPE in the face of remelting, annealing, or sequential annealing. While in vivo oxidation was higher in the tibial retrievals than in the acetabular liners, the debate regarding this topic continues.…”
mentioning
confidence: 99%